The ABC's of PHD /c Hj. Kamaruzaman Jusoff & Fareiny Morni - Kamaruzan Jusoff; Fareiny Morni (Penerbit Universiti Putra, 2010)
The book covers all bases in 14 concise chapters. Couched in simple terms and simple language, the book provides readers with a guide which begins with an introductory caution on being prepared for the task. In this book, the authors endeavor to build awareness and better understanding of the qualities and character building attributes required in striving for academic excellence.